AN ANALYSIS OF STUDENTS' DIFFICULTIES IN WRITING DESCRIPTIVE TEXT - Bobby Pramjit Singh Dhillon; Masta Magdalena; Henni Natalina Sijabat; Bernieke Damanik (Merwin Publisher, 2023)
In classroom practice, most students think that writing is difficult. It is because in writing there are some important components such as vocabulary, spelling, punctuation, and grammar. The objectives of this research to know the ability and the difficulties of students in writing descriptive text. The research designed this study with quantitative method with the data from students’ writing test. The findings show that: the students’ ability in writing descriptive, the total mean score of the students was 12.5. It means that the students’ ability in writing descriptive text was classified as very poor. The mean score of the students writing ability in content categories was 2,63. It was classified very poor. The mean score of the students in organization was 2,09. It was classified very poor. The mean score of the students in vocabulary was 2.93. It was classified very poor. The mean score of the students in grammar was 1,75. It was classified very poor. And the mean score of the students in mechanic was 12,5. It was classified very poor. The students’ difficulties in writing descriptive text consist of describing object in detail and grammar mastery such as simple present tense.